The Metabolism of Organic Acids by a Marine Pennate Diatom - Cooksey, Keith E. (1972)
Cocconeis diminuta, a marine benthic diatom, metabolizes acetate and lactate-(14)C. In the light, the major product was lipid, whereas in the dark, CO(2) was the major product. Analysis of proteins synthesized in the presence of acetate or lactate showed that radioactivity was incorporated predominantly into the glutamate family of amino acids and those amino acids related directly to the substrate. Light and dark assimilation of substrate was inhibited slightly by 3-(3′,4′-dichlorophenyl)-1,1-dimethylurea and 2,4-dinitrophenol. 3-(3′,4′-Dichlorophenyl)-1,1-dimethylurea caused a pattern of metabolism of acetate in the light characteristic of that which occurs in the dark. Monofluoroacetic acid inhibited assimilation considerably in the dark, but less in the light. The level of enzymes of the tricarboxylic acid cycle and NADH-oxidase were found to be about the same as those in other autotrophs. The metabolism of acetate and lactate is discussed in relation to the autotrophic mode of nutrition of Cocconeis diminuta.